Information technology and societal development [ - Targowski, Andrew , 1937- (Information Science Reference, 2009)
"This book investigates the role of information and communication in civilization's development, because it is information and communication that decide how human organization, knowledge, and wisdom are applied in decisions impacting human survival"--Provided by publisher.